Lyapunov-Based Mode Predictive Control o a PUC7 Grid-Connected Multilevel Inventer - Makhamreh, Hamza; Sleiman, Mohammad; Kukrer, Osman; Al-Haddad, Kamal (IEEE-Inst Electrical Electronics Engineers Inc, 2019)
In this paper, a new Lyapunov-based model predictive controller is proposed for a 7-level packed U-cell (PUC7) grid-connected inverter. A cost function of the proposed model predictive controller is designed from the system stability point of view, inspired by the Lyapunov control theory. The proposed controller eliminates the need for gains that are associated with cost function coefficients, as seen in classical model predictive control based controllers. Therefore, the control design problem is significantly simplified. In addition, the average switching frequency is also reduced, as shown in both simulation and experimental results, leading to a reduction in switching losses. Simulation and experimental tests, on a PUC7 lab prototype, demonstrate the excellent performance of the proposed control system, in terms of high disturbance rejection. robustness to parameter mismatches, and fast dynamic response. Such features qualify the proposed control strategy as a good candidate for grid-tied applications.
Keywords: Lyapunov control; model predictive control (MPC); multilevel converter; packed U-cell inverter